2005
DOI: 10.1016/s1726-4901(09)70136-4
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Zygapophyseal Joint Injections in Patients with Chronic Lower Back Pain

Abstract: Lumbar zygapophyseal joint injections, as a useful diagnostic tool for facet joint syndrome, could also have useful palliative effects in the management of chronic lower back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…Though the pain response gradually declines over time, even in the medium term (up to 24 weeks) as many as one-third of patients still experience significant pain relief. [10121718] Our results showed short-term relief in 86–93% of patients and medium-term relief in 62%, which compare favorably with the results of these earlier studies. In our opinion, the high number of responders in our study could be due to meticulous adherence to the patient selection criteria, with elicitation of paraspinal tenderness over the facet joint being the most important inclusion criterion.…”
Section: Discussionsupporting
confidence: 90%
“…Though the pain response gradually declines over time, even in the medium term (up to 24 weeks) as many as one-third of patients still experience significant pain relief. [10121718] Our results showed short-term relief in 86–93% of patients and medium-term relief in 62%, which compare favorably with the results of these earlier studies. In our opinion, the high number of responders in our study could be due to meticulous adherence to the patient selection criteria, with elicitation of paraspinal tenderness over the facet joint being the most important inclusion criterion.…”
Section: Discussionsupporting
confidence: 90%
“…Other possible mechanisms of facet joint pain are chronic synovial reactions and degenerative osteoarthritis. 32 In our opinion, this supports our theory that the extended removal of the intervertebral disc represents the ''major trauma'' with consecutive reduction of the intervertebral space, which potentially leads to progressive disruption of spinal stability. Recently, Parker et al calculated the enormous costs of treatment of long-term back pain in postsurgical patients with single-level LDH 33 , and the factors that sensitize patients to the postsurgical risk of spinal instability.…”
Section: Pfjs and Discectomysupporting
confidence: 82%
“…Several studies demonstrated the positive short and long- term effects of IA LFJ corticosteroid injection for managing LFJ pain. [10,13,14] In contrast, Lilius et al [29] reported no differences in outcome between the placebo and ICI groups. Generally, to clinicians, the level of evidence of ICIs is fair or moderate.…”
Section: Discussionmentioning
confidence: 99%
“…The intra-articular (IA) LFJ injection or lumbar medial branch block (MBB) with corticosteroid is widely and conventionally used for the management of LBP originating in the LFJ. [914] However, the levels of evidence for these procedures are considered fair or moderate. [15] Furthermore, corticosteroids can have several adverse effects.…”
Section: Introductionmentioning
confidence: 99%